A critical review of the jurisprudence of laws on rape in Nigeria and the impact of statute of limitations on prompt reporting of rape incidents. Issue 2 (3rd April 2019) - Amucheazi, Chibike Oraeto
Abstract : As high-profile cases of rape continue to make headlines in Nigeria and beyond-and as rape survivors appear to relent in reporting crimes- it can help to have a better understanding of the laws on rape and the reasons for delayed report of the crime as well as the effect of the statutory time frame within which legal actions can be instituted against perpetrators of rape. One effective way to curb or exterminate the menace of rape is by effective prosecution and punishment of offenders. However limitation statutes may deny citizen's access to justice and it seems not to propel prompt report of rape incidents. This paper examines the Nigerian criminal law of rape and attempts a critical analysis of limitation statutes in selected forums in order to establish its probative value on reporting rape whilst identifying the reasons for delay in report and MEASURES to address same. Materials and methods: materials consulted are statutes, case laws and relevant literatures. Method applied is doctrinal methods and desk based/internet research. Results: probative and qualitative information on the state of the art in concerned areas researched on.